The Influence of Pain Intensity and Executive Functioning on Facial Pain Expression - Traxler, Juliane (Student Undergraduate Research E-journal!, 2016)
Facial pain expressions are frequently used to assess pain in populations that cannot verbally express their suffering. The present study aimed to investigate the usefulness of facial expressions as an assessment tool and the influence of executive functioning on facial pain expression. Pain ratings to mechanical nociceptive stimuli were obtained from 57 healthy elderly, facial pain expressions were filmed and coded, working memory and cognitive inhibition were assessed. Results showed a positive correlation between stimulus intensity and pain expressions which was moderated by cognitive inhibition. Pain intensity has a stronger effect on facial pain expression at low levels of inhibition.